Advances in fetal echocardiography. Issue 2 (April 2018) - Gardiner, Helena M.
Abstract: The development of fetal echocardiography and success in prenatal cardiac screening programs over the past 30 years has been driven by technical innovation and influenced by the different approaches of the various specialties practicing it. Screening for congenital heart defects no longer focuses on examining a limited number of pregnant women thought to be at increased risk, but instead forms an integrated part of a high-quality anatomical ultrasound performed in the second trimester using the 'five-transverse view' protocol. A prenatal diagnosis is feasible in almost all cardiac lesions and the advantages to parents and to health professionals are well recognized. Prenatal evaluation can usually determine the level of care required at delivery, thereby reducing perinatal morbidity. However, only half of the babies undergoing surgery within the first year of life have a prenatal detection, and practical training programs to support and provide feedback to sonographers remain essential for continued improvement. Highlights: Prenatal cardiac screening, using five-transverse views, should be part of the anatomy scan, available to all pregnant women. Successful fetal screening programs include practical training, audit and feedback to sonographers from the fetal center. A prenatal diagnosis enables delivery in a safe environment with the appropriate skilled personnel close by. Exercise caution and good practice in first trimester ultrasound screening and recognize its potential pitfalls and dangers.